Harnessing Quality for Global Competitiveness in Eastern Europe and Central Asia - Racine, Jean-Louis (World Bank, 2012)
In many countries in Eastern Europe and Central Asia (ECA), the National Quality Infrastructure (NQI) does not support business competitiveness, though this is one of its functions in organization for economic co-operation and development countries. In most of the Commonwealth of Independent States (CIS) countries, it even impedes competitiveness. The most common economic benefits of adopting standards include increased productive and innovative efficiency. Standards lead to economies of scale, allowing suppliers to achieve lower costs per unit by producing large, homogeneous batches of products. Standards spur and disseminate innovation, solve coordination failures, and facilitate the development of profitable networks. Participation in world trade increasingly requires that suppliers comply with standards determined by lead buyers in global value chains. The nature of participation in the global economy has changed dramatically over the past two decades. Rarely do producers turn raw materials into final products and sell them directly to customers. Improving the quality of goods and services and diversifying into sectors where quality matters can be a sustainable source of global competitiveness. Some of the productive tasks associated with high-quality goods have high learning and technological externalities. In those sectors, producers tend to form tight relationships with global buyers who transfer their knowledge and support the producers' quality-upgrading processes. Diversifying into a broad range of sectors also reduces macroeconomic volatility, but quality upgrading becomes necessary to enter new sectors that compete on quality.